Sonochemical degradation of endocrine-disrupting organochlorine pesticide Dicofol: Investigations on the transformation pathways of dechlorination and the influencing operating parameters. (August 2018) - Debabrata, Panda; Sivakumar, Manickam
Abstract: Dicofol, an extensively used organochlorine pesticide and a recommended Stockholm convention persistent organic pollutant (POP) candidate is well known for its endocrine disruptive properties. The sonochemical degradation of Dicofol in aqueous media has been investigated using a 20-kHz probe type sonicator with power inputs from 150 to 450 W. The degradation rate was determined as a function of concentration of Dicofol, solution pH, bulk phase temperature, ultrasonic power density and H2 O2 addition. At optimum operating conditions, the pseudo-first-order degradation rate constant (k) was determined to be 0.032 min −1 and the extent of degradation was found to be 86% within 60 min of ultrasound treatment. High performance liquid chromatography (HPLC) and Gas chromatography coupled with mass spectroscopy (GC-MS) analysis indicated the presence of degraded products. The obtained results of Dicofol degradation and control experiments in the presence of H2 O2 and radical scavenger test suggest thermal decomposition along with radical attack at bubble-vapor interface to be the dominant degradation pathway. Sonochemical treatment is effective and promising for successful removal of harmful pesticides such as Dicofol and superior removal efficiency for other POPs is expected in the near future with the successful implementation of ultrasound-based wastewater treatment. Graphical abstract: Image 1 Highlights: Degradation of Dicofol by sonolysis is effective. Degradation of Dicofol increased linearly with ultrasonic power up to 375 W. HPLC and GC-MS analyses demonstrated the presence of degraded products. Dicofol removal of 86% was achieved within 60 min of sonochemical treatment.